Trapped in an information provision gap? A scoping review of (unmet) information needs, preferences, and behaviors among long-term cancer survivors - Hopfe, Elisabeth; Baumann, Eva; Grünwald, Viktor; Sadeghi Shakib, Fereshteh; Dirksen, Uta (Frontiers in Communication, 2025)
A scoping review was conducted to gain a more comprehensive understanding of the unmet needs and communication challenges faced by long-term cancer survivors. Information seeking, barriers, and avoidance behaviors were reflected. Following the PRISMA-ScR guidelines, five databases were searched. Of 1,041 articles, 36 met the eligibility criteria. Studies focused on breast and prostate cancer survivors (50%) and survivors residing in North America and Canada (56%). Information needs mainly referred to specific cancer types, recurrence, sexual functioning, fertility, and comorbidities. Information barriers include concerns about trust in information quality, information overload, and difficulties in finding and understanding information. Most survivors are active information seekers, but some also exhibit information avoidance. Survivors prefer information from their healthcare provider or the Internet, as well as medical information and experiences from other survivors. Further research is needed on survivors from vulnerable groups, CAYAs (children, adolescents, and young adults), and ethnic minorities.